2020
DOI: 10.1016/j.nicl.2020.102486
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function relationship of the posterior subthalamic area with directional deep brain stimulation for essential tremor

Abstract: Highlights Directional DBS of the DRTT and the zona incerta is correlated with tremor suppression. Activation patterns for tremor suppression and side effects involve mostly the dentato-rubro-thalamic tract and the zona incerta. Concomitant side effects often limit the therapeutic window of directional deep brain stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…There was also little or no activation of the LF and TF. These subject-specific pathway activation modeling results confirm previous studies based on 3T MRI and volume of tissue activated calculations that found positive association with the CTT region and tremor reduction [ 22 - 25 , 30 , 31 , 68 - 70 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There was also little or no activation of the LF and TF. These subject-specific pathway activation modeling results confirm previous studies based on 3T MRI and volume of tissue activated calculations that found positive association with the CTT region and tremor reduction [ 22 - 25 , 30 , 31 , 68 - 70 ].…”
Section: Discussionsupporting
confidence: 89%
“…Biophysical modeling of DBS has become an important tool to identify relationships between the volume of tissue activated [ 29 , 30 ] or the predicted pathways activated [ 31 - 33 ] and the resulting clinical efficacy and side effects of each stimulus setting. Recent studies have shown that pathway activation models, which directly simulate multi-compartment axonal membrane dynamics, are significantly more accurate compared to activating function and driving-function based methods [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…As anatomical landmark feature, we set the minimum distance (Euclidean distance) of the contact center to a previously published volume of tissue activated (VTA)-based anatomical reference point (stimulation sweet spot indicating a low effect threshold) within the normalized space of the motor STN (Montreal Neurological Institute x: 12.5838 y: −12.4868 z: −6.2879). 30 Lead reconstruction was performed with the Lead-DBS toolbox 31,32 (details in the Supplementary Material).…”
Section: Spatial-electrophysiological Processingmentioning
confidence: 99%
“…The most commonly reported stimulation-related adverse effect was dysarthria (20-57%), followed by spasms (34%) and postural instability (16-29%) of the electrodes implanted in the cZi/PSA. In addition, oculomotor side effects and paresthesias have been described in 19% and 11-14%, respectively [54,59,65,66].…”
Section: Dbs For Essential Tremormentioning
confidence: 99%